Potensi Penerapan Konsep Aerotropolis pada Kawasan Bandara Internasional Sultan Hasanuddin - Fitriah Khairunnisa M.; Arifuddin Akil; Ihsan Ihsan (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2019)
Aerotropolis is a model to answer new economic needs in terms of connectivity, speed, and agility. Aerotropilis on the runway sees the airport not only as a runway up and down the runway can give effect to the spread around the airport and become a stimulant generator on economic growth in the community. The purpose of this study is to find out the potential application of the concept of aerotropolis through the principles of aerotropolis development, then from these results it can be approved the direction of further development. This research uses comparative, spatial, and AHP analysis methods. Based on the results of the analysis, from several aerotropilis planning principles related to the four principles that are not appropriate, namely (1) Principles of spatial planning, (2) Principles of land use, (3) Principles for the main designation in the area, (4) Principles for the provision of business services. To make Sultan Hasanuddin airport become an aerotropolis, it is necessary to develop a system to fight the commercial dominant, as well as provide business areas and make the airport area the center of activity or the same as the city center.